Disease Recurrence After Early Discontinuation of Eculizumab in a Patient With Atypical Hemolytic Uremic Syndrome With Complement C3 I1157T Mutation. Issue 3 (April 2016) - Toyoda, Hidemi; Wada, Hideo; Miyata, Toshiyuki; Amano, Keishiro; Kihira, Kentaro; Iwamoto, Shotaro; Hirayama, Masahiro; Komada, Yoshihiro
Abstract : Eculizumab, terminal complement inhibitor, has become the frontline treatment for atypical hemolytic uremic syndrome (aHUS). However, the optimal treatment schedule has not yet been established. We describe here an aHUS patient with a mutation of C3 I1157T who achieved remission with eculizumab and suffered a recurrence after eculizumab discontinuation, a clinical situation that has not been previously described in patients with C3 mutation. A 9-year-old male experienced an onset of aHUS after viral gastroenteritis and was treated with hemodialysis. At 13 years of age he developed bacterial enterocolitis due to Campylobacter jejuni and experienced a recurrence of aHUS. Eculizumab was initiated on day 4 after disease onset resulting in recovering laboratory parameters. The patient received eculizumab for 5 months before its discontinuation. Second relapse induced by bacterial pharyngitis was confirmed 4 months after eculizumab discontinuation and prompt eculizumab reinitiation resulted in rapid remission. The patients carrying mutations in CFH or C3 have a high frequency of relapse and worse prognosis. More than 50% of aHUS relapses occurred during the first year after the onset. Therefore, long-term treatment with eculizumab is appropriate in patients with aHUS who have experienced a relapse or have mutations associated with poor prognosis.